Cómo organizar la red de comunicaciones (Bruselas, 2015)
"This second in a series of manuals for European Workers' Representatives explains in an easy-to-read format how European Works Council (EWC) members can organise and manage their communications network. It gives tips and tricks for better information flows and provides examples of best practices in several EWCs. The manual is available in 8 different languages."